Da detecção à intervenção precoce em casos de risco ao desenvolvimento infantil e distúrbio de linguagem - Oliveira, Luciéle Dias (2013)
The following research is circumscribed to three subjects who suffer from language disorder. It approaches the process of early detection of risks to development and identification of the language disorder by the family and/or health professionals, as well as discussing aspects of how language works for these subjects. The body of this research is the analysis of how the process between detection of risk by health professionals and establishment of therapeutic demand by the family happens. To make this analysis possible, three babies were selected all three in risk of development. The first subject: a baby with obvious biological risk (prematurity) and had an early intervention; the other two babies don t had biological risk (not premature, nor lesions or syndromes) for language. The last two babies were not subjected to an early intervention and had late speech-language therapy. For this study, interviews were conducted with the aim of gathering general data on the subjects health, with the main focus on matters of communication and language. Footage of the subjects was also taken, in which a scenario was created and organized with the babies favorite toys, with themes related to child contemporary world, with the objective of analyzing how the subjects language worked. The episodes were used to analyzing how the subject s language worked. The footage was transcribed orthographically and language data presented in tables that identify the shifts of the interlocutors involved. The cases were analyzed as they unfolded, in a singular manner in what concerns symptom detection and language functionality, as well as the demand for speech-language therapy. In all cases, it s important to notice the baby-adult intersubjectivity, specially of mothers in the process of language acquirement, as early as the first protoconversations. Moreover, it s important to raise awareness of the effects of early intervention, particularly the process of symptom detection, as well as stabilizing the child s language with the aim of reducing symptoms.